Pendekatan Antropologi Agama dan Kegunaanya Terhadap Kajian Living Hadis: Pendekatan Antropologi terhadap Agama dan Pemanfaatannya dalam Studi Hadis Hidup - Lubis, Muhammad Fikri (Transformatif, 2025)
This article contains research on the role of the anthropology of religion approach in the study of living hadith which is useful as a lens in viewing the reception and practice of society that departs from the sacred texts in Islam, especially the hadith. This study aims to explain the substance of religious anthropology and its role as an approach in studying the reception aspect of society, especially the phenomenon of the practice of social symptoms that originate from the hadith. This research is multidisciplinary in nature that integrates two scientific objects, namely anthropology and hadith studies, the meeting point between the two is the social aspect that cannot be separated from the two sciences, this research is based on literature studies by collecting primary and secondary data sources and collecting information from the results of observations of several community practices as research objects. The results of the study explain that through the anthropology of religion approach, the background of the practices and phenomena of a community group can be objectively known which departs from the doctrine of sacred texts, especially the hadith, then creates a construction of practices that develop from generation to generation and continue to run even though the community does not know that what is practiced is actually sourced from the sacred text.